2017
DOI: 10.1016/j.ajog.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, birth, and infant outcomes by maternal fertility status: the Massachusetts Outcomes Study of Assisted Reproductive Technology

Abstract: Background Births to subfertile women, with and without infertility treatment, have been reported to have lower birthweights and shorter gestations, even when limited to singletons. It is unknown whether these decrements are due to parental characteristics or aspects of infertility treatment. Objective To evaluate the effect of maternal fertility status on the risk of pregnancy, birth, and infant complications. Study Design All singleton live births of ≥22 weeks’ gestation and ≥350 grams birthweight to Mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 109 publications
9
88
3
2
Order By: Relevance
“…Higher plurality, though, is associated with much greater risks of pregnancy, birth, and infant adverse health outcomes compared to singletons. Comparing the outcomes in this study to the analysis of 459,623 singleton births in the MOSART project during this same time period (2004–10) (38), show the manifold increased risks of twins compared to singletons. Born an average of 3 V weeks earlier and 950 grams lighter, twins were more than ten times as likely to be born very low birthweight, low birthweight, or early preterm, and eight times more likely to be born preterm.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Higher plurality, though, is associated with much greater risks of pregnancy, birth, and infant adverse health outcomes compared to singletons. Comparing the outcomes in this study to the analysis of 459,623 singleton births in the MOSART project during this same time period (2004–10) (38), show the manifold increased risks of twins compared to singletons. Born an average of 3 V weeks earlier and 950 grams lighter, twins were more than ten times as likely to be born very low birthweight, low birthweight, or early preterm, and eight times more likely to be born preterm.…”
Section: Discussionmentioning
confidence: 61%
“…We used similar methods to that described in the singleton analysis using this same study population (38). The study design and setting, data sources, variables, and statistical analysis are similar, except for the additional provisions made for categorizing and analyzing twin pregnancies and twin infant pairs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large observational studies identified that ART pregnancies are associated with a significant risk of complications as compared with pregnancies after spontaneous conception (SC). These complications include preterm delivery, low birthweight, intrauterine growth restriction, gestational diabetes, pre‐eclampsia, fetal loss and placental anomalies . Although initially it was believed that these complications were more prevalent after ART due to the high incidence of multiple pregnancies, a high risk of these complications was also demonstrated in ART singleton pregnancies …”
Section: Introductionmentioning
confidence: 99%
“…In the last 2 years there have been a substantial number of published studies that evaluate the association of placental anomalies with ART pregnancies . Considering the marked increase in published data, a systematic appraisal of the available evidence was considered essential in order to confidently evaluate this proposed higher risk of placental anomalies after ART.…”
Section: Introductionmentioning
confidence: 99%